2018
DOI: 10.3892/mmr.2018.8532
|View full text |Cite
|
Sign up to set email alerts
|

Expression level and potential target pathways of miR-1-3p in colorectal carcinoma based on 645�cases from 9 microarray datasets

Abstract: For the purpose of demonstrating the clinical value and unraveling the molecular mechanisms of micro RNA (miR)-1-3p in colorectal carcinoma (CRC), the present study collected expression and diagnostic data from Gene Expression Omnibus (GEO), ArrayExpress and existing literature to conduct meta-analyses and diagnostic tests. Furthermore, the potential targets of miR-1-3p were attained from datasets that transfected miR-1-3p into CRC cells, online prediction databases and differentially expressed genes from The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Previous studies have clarified the irregular expression levels of several miRNAs in RCC together with miR-1-3p. miR-1-3p have been validated to be reduced in numerous different types of cancer, including lung cancer,54 colorectal carcinoma55, and urinary neoplasms. But the role and function of miR-1-3p in malignancy disease have not been definitely illuminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have clarified the irregular expression levels of several miRNAs in RCC together with miR-1-3p. miR-1-3p have been validated to be reduced in numerous different types of cancer, including lung cancer,54 colorectal carcinoma55, and urinary neoplasms. But the role and function of miR-1-3p in malignancy disease have not been definitely illuminated.…”
Section: Discussionmentioning
confidence: 99%
“…But the role and function of miR-1-3p in malignancy disease have not been definitely illuminated. Wang et al, revealed that miR-1-3p inhibit lung cancer by c-Met signaling and EMT process 55. Gao et al, demonstrated that miR-1-3p inhibits cell proliferation and invasion by regulating the BDNF-TrkB signaling pathway in bladder cancer 56.…”
Section: Discussionmentioning
confidence: 99%
“… 23 miR-1-3p is downregu-lated by hypoxia in pulmonary artery smooth muscle cells and contributes to the development of pulmonary vascular remodeling. 24 miR-1-3p was downregulated in various types of cancer, such as prostate cancer, 25 oral squamous cell carcinoma (OSCC), 26 bladder cancer, 27 colorectal carcinoma, 28 and lung cancer, 29 where miR-1-3p regulated the proliferation and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ectopic expression of miR-1 inhibits prostate cancer cell growth, epithelial-mesenchymal transition and bone metastasis [ 18 , 19 ]. In addition, miR-1-3p has been reported to suppress tumor growth in colon carcinomas [ 20 ], decrease cellular proliferation and migration of oral squamous cell carcinoma [ 21 ], inhibit cell proliferation and invasion and induce apoptosis in bladder cancers [ 22 ]. These data indicate a potential tumor suppressive function of miR-1-3p.…”
Section: Introductionmentioning
confidence: 99%